A comparison of social processes at three sites of the French Rhône River subjected to ecological restoration. (28th March 2015) - Barthélémy, Carole; Armani, Gilles
Summary Understanding social processes (trajectories of relationships among stakeholders), political constraints, cultural aspects and public opinions is essential for efficient design, sustainability and evaluation of restoration operations. However, few restoration projects involve the participation of social sciences. The ecological restoration of the Rhône River involved increasing flow below dams and better connecting floodplain channels at multiple sites along the river. Therefore, it provided a unique opportunity to identify the commonalities and differences among social processes associated with ecological restoration. We used qualitative analyses of speeches and interviews with stakeholders to understand their relationship to the Rhône. These analyses revealed that social values, relating local residents to the river, played a major role throughout the restoration projects. The comparison of social processes among three sites of the Rhône shows that they generally followed three stages: managing a crisis, transforming the relationship to the river and valuing the local social space (the territory). Consistent patterns emerging across sites included the following: (i) the role of a local public figure able to mobilise stakeholders in supporting the restoration project; (ii) the importance of the organisation of the stakeholder community and its commitment to the project; and (iii) the major role of interactions between local and national levels. Variation across sites also occurred and may be related to unforeseen events such as political changes and natural hazards (e.g. floods and pollution). Involving social science in restoration projects requires taking into account commonalities in social processes as well as the diversity of local experiences.